Development of Moral Journey Map Media to Improve Student Understanding Based on Design Thinking and User Experience - Durrotul Hikmah Yuliangsih; Roisna Kamila; Abdul Khobir; Nok Uzana; Khaerun Umam; Muhammad Ma’ruf (FITK UIN Walisongo Semarang, 2026)
This study was motivated by the low level of student engagement in the learning process due to the use of conventional methods and learning media that lack interactivity. The study aims to analyze user needs, design, and develop a “Character Development Roadmap” media based on Design Thinking and User Experience (UX) to enhance students' understanding. The study employs a Research and Development (R&D) approach with Design Thinking stages, including empathize, define, ideate, prototype, and test. The study subjects consisted of 40 students from MTs TMI Wonopringgo. Data collection techniques included observation, interviews, questionnaires, and pretest and posttest assessments. The results indicate that students require learning media that is more interactive, contextual, and game-based. The developed media consists of a visual treasure map and a game featuring a progressive challenge system that integrates elements of game-based learning and User Experience (UX). Descriptive statistics revealed an increase in the students’ mean score from 39.28 on the pretest to 42.15 on the posttest. The results of the paired sample t-test yielded a significance value of 0.048 < 0.05, indicating a significant difference between the pretest and posttest results. Thus, the Moral Journey Map media demonstrates good potential in helping students understand learning materials through a more interactive and contextual learning experience.